Effect of doping in SrTiO3:BiFeO3 binary system. (2021) - Patel, Nima H.; Shah, Manali; Shah, Devang D.; Mehta, P.K.
Abstract: The structural and Impedance studies of ferroelectric BiFeO3 (BFO) and paraelectric SrTiO3 (STO) perovskite compounds are reported here. The XRD is performed to confirm the phase formation of prepared samples. The XRD patterns have shown that these materials crystallize and the overall structure remains unaltered with increment in concentration of BiFeO3 . Dielectric analysis (Impedance spectroscopy) of the prepared materials shows a normal dielectric behaviour like other ceramic compounds and the dielectric constant as well as the dielectric loss of the sample is encouraging for the intermediate composite 0.5BFO + 0.5STO for end industrial application.